2019
DOI: 10.1248/bpb.b18-00951
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose-Induced Apoptosis in Human Kidney Cells Was Alleviated by miR-15b-5p Mimics

Abstract: MicroRNAs were involved in a wide range of biological processes of diabetic nephropathy (DN). It is reported that miR-15b-5p was downregulated in the patients with DN. However, the mechanisms underlying the regulatory effects of miR-15b-5p on patients with diabetes remain unclear. Thus, this study aimed to investigate the role of miR-15b-5p during high glucose (HG)-induced apoptosis in human kidney cells. Quantitative real-time (qRT)-PCR was used to detect the level of miR-15b-5p. CCK-8 assay, EdU staining ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…One report claimed that miR-15b-5p could reduce HG-induced podocyte injury by repressing inflammation response, oxidative stress, and apoptosis of podocyte via downregulating Sema3A [22]. Shen et al revealed that miR-15b-5p overexpression could reduce apoptosis in human kidney cells induced by HG [23]. Herein, CDKN2B-AS1 was proved as a sponge for miR-15b-5p in HMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One report claimed that miR-15b-5p could reduce HG-induced podocyte injury by repressing inflammation response, oxidative stress, and apoptosis of podocyte via downregulating Sema3A [22]. Shen et al revealed that miR-15b-5p overexpression could reduce apoptosis in human kidney cells induced by HG [23]. Herein, CDKN2B-AS1 was proved as a sponge for miR-15b-5p in HMCs.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-34a could contribute to renal fibrosis through decreasing klotho expression in HK-2 cells [21]. It was reported that miR-15b-5p exerted a protective role in DN [22,23]. As far as we know, the targeting relationship between CDKN2B-AS1 and miR-15b-5p in DN is unclear.…”
Section: Introductionmentioning
confidence: 98%
“…The etiology of DN has not been fully elucidated, and it is believed that the release of many cytokines and reactive oxygen species from MC cells were induced by high glucose resulting from disorders of glucolipid metabolism, which subsequently causes oxidative stress, rheological changes and inflammatory responses in glomeruli, resulting in cell proliferation and division, leading to the Trop J Pharm Res, September 2021; 20 (9): 1824 aggregation of extracellular matrix in MC cells and reducing renal function [12]. NF-κB is an important nuclear transcription factor in the nucleus that regulates the activation and expression of many genes, and participates in the signal transmission of cellular inflammatory response [13]. It was discovered that NF-κB was involved in the process of renal injury in DN via induction of inflammatory response and production of vascular endothelial growth factor [14].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, PKCβ2 knockdown inhibited the expression levels of pERK, JNK and p38. Therefore, PKCβ2 knockdown weakens ERK/JNK/p38 pathway activation in meglumine diatrizoate and AGEs-induced HK-2 cells (24,25). Autophagy is a key biological phenomenon involved in the development and growth of organisms (26).…”
Section: Discussionmentioning
confidence: 99%